A systematic review and meta-analysis of patient education in preventing and reducing the incidence or recurrence of adult diabetes foot ulcers (DFU). Issue 5 (May 2018) - Adiewere, P.; Gillis, R.B.; Imran Jiwani, S.; Meal, A.; Shaw, I.; Adams, G.G.
Abstract: Background: The World Health Organization (WHO) states that diabetic foot ulcers (DFU) are associated with disability, death among patients with diabetes and substantial costs, if not prevented or managed effectively. The aim here is to examine the effectiveness of patient education in preventing and reducing the incidence or recurrence of adult DFU and amputation. Methods: A systematic review and meta-analysis of randomised clinical trials (RCTs) in adults aged 18+ who have diabetes mellitus (type 1 or type 2) or DFU. CINAHL, EMBASE, MEDLINE, PSYCINFO, Cochrane Library and Evidence-Based Nursing, National Library for Health, Medica and Google Scholar were searched. Only English language studies were considered. Databases were searched from their inception to September 2017. Findings: Six RCTs met the inclusion criteria. Only five RCTs reported on the incidence of DFU whilst only two reported on amputation rates. There was no advantage of combining different educational approaches in preventing/reducing DFU, relative risk (RR) of 0.50 (95%CI 0.21, 1.17) (P = 0.11). Two RCTs based on foot care education alone were compared with usual care; the result showed a non-significant effect (P = 0.57) with high heterogeneity of 77%. Analysis based on intensive versus brief educational approach showed a statistically reduced risk of incidence of DFU in the intervention group when compared to the control group; (RR, 0.37, 95%CI 0.14, 1.01) (P = 0.05) with high heterogeneity of 91%. Interpretation: The intensive educational intervention was associated with reduced incidence of DFU.